The new baby care book - Stoppard, Miriam (Dorling Kindersley Book, 1990)
A new, revised and updated edition of the essential guide to caring for and coping with your baby during the first three years of life. It provides straightforward, sensible solutions to the problems which any new parent is likely to face.